Paroxysms at Stromboli Volcano (Italy): Source, Genesis and Dynamics - Métrich, Nicole; Bertagnini, Antonella; Pistolesi, Marco (Frontiers in Earth Science, 2021)
For nearly 1300 years Stromboli has been renowned not only for its continuous degassing activity and mild explosions at the summit craters, but also for short-lived, violent explosive events of variable scale known as major explosions and paroxysms. It is important to understand the triggering mechanisms of paroxysms, as this violent explosive activity can impact social and economic life on the island. To this end, we focus on the 1456 and 1930 paroxysms and on the most recent events, in July and August 2019. We present new data on the geochemistry of the 2019 bulk pumice, along with a compilation of data from the literature, chemical profiles in olivine crystals, and the physical parameters of explosive eruptions of wide ranging magnitude and intensity. Trace element concentrations (Nb, La and Ba) and ratios (Rb/Th) indicate that the 2019 pumice samples plot in the domain of magma batches erupted within the last 20 years at Stromboli. As a whole, there is no correlation between magma geochemistry and magnitude or intensity of explosive eruptions, which span a range of ~3 orders of magnitude (from major explosions to large paroxysms) based on estimates of erupted tephra volumes. In contrast, olivine compositions are a good proxy for total tephra volumes, suggesting that the magma source can affect the magnitude and intensity of the final eruption. They also indicate that in July 2019 the plumbing system reached steady-state conditions prior to paroxysm, whereas olivine and clinopyroxene zoning in products from the August 2019 paroxysm testifies to magma recharge. For small and large paroxysms, timescales were derived from Fe-Mg diffusion profiles in olivine. In both types of explosion, the last phases of crystallization indicate rapid magma ascent rates two to ten days prior to eruption. Lastly, we discuss the possible relative influence on eruption dynamics of flank collapse, lava outpouring through fractures opening, and partial emptying of the shallow conduits. These phenomena may enhance volatile-rich magma ascent by increasing the decompression rate, although pressurization of the crustal system and the deep refilling by magma and its CO2-rich gas phase play a major role in triggering paroxysms.